2005
DOI: 10.1113/jphysiol.2004.078212
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal masculinization alters the HPA axis phenotype in the adult female rat

Abstract: The ability of postnatal testosterone propionate (TP) to masculinize both behaviour and gonadal cyclicity in the female rat is well documented. We have investigated whether postnatal androgen also has an organizational effect on another sexually dimorphic neuroendocrine system -the hypothalamo-pituitary-adrenal (HPA) axis. Female rats were exposed to a single injection of testosterone propionate (TP) or oil within 24 h of birth. As adults, rats were either ovariectomized and given 17β-oestradiol replacement (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 59 publications
1
45
1
2
Order By: Relevance
“…Testosterone treatment of females at birth alters the phenotype of the hypothalamic-pituitary-adrenal axis (Seale et al, 2005), the morphology of sexually dimorphic brain regions (Han and De Vries, 2003;MacLusky et al, 1987;Morris et al, 2004;Roselli and Klosterman, 1998) and affects certain aspects of learning (Roof, 1993;Roof and Havens, 1992;Shors and Miesegeas, 2002;Williams and Meck, 1991). Therefore, we were surprised that learned helplessness behavior did not emerge in females that were masculinized at birth.…”
Section: Sex Differences In Helplessnessmentioning
confidence: 99%
“…Testosterone treatment of females at birth alters the phenotype of the hypothalamic-pituitary-adrenal axis (Seale et al, 2005), the morphology of sexually dimorphic brain regions (Han and De Vries, 2003;MacLusky et al, 1987;Morris et al, 2004;Roselli and Klosterman, 1998) and affects certain aspects of learning (Roof, 1993;Roof and Havens, 1992;Shors and Miesegeas, 2002;Williams and Meck, 1991). Therefore, we were surprised that learned helplessness behavior did not emerge in females that were masculinized at birth.…”
Section: Sex Differences In Helplessnessmentioning
confidence: 99%
“…[67][68][69] In rodents, early androgen exposure disrupts feminine behavior, gonadotropin release and neuroanatomical sexual differentiation 70,71 and suppresses the HPA axis, 72 whereas in human, prenatal estrogen administration, that is, by DES, was found to increase the risk of affective disorders. 73,74 These observations, together with our present data raise the possibility that androgens may also play a role, either via direct or indirect effects, in prenatal programming and in activity of the adult CRH neurons, and may thus be involved in the sex differences in the stress response and in the risk for mood disorders.…”
Section: Mmtv-arementioning
confidence: 99%
“…First, there is the neonatal period during which it appears that exposure to sex steroids can programme adult HPA activity (Schapiro 1965, Levine & Mullins 1967, Patchev et al 1995, Romeo et al 2004, Seale et al 2005 and also puberty during which time a non-sex steroid-dependent maturational process takes place allowing the development of a stimulatory effect of oestrogens on HPA activity.…”
Section: Discussionmentioning
confidence: 99%
“…Masculinised female rats have increased body weight (Swanson & van der 1963), failed to display lordosis during sexual activity and are permanently sterile (Gerall & Kenney 1970, McDonald & Doughty 1972. On the basis of this research, along with the evidence demonstrating susceptibility of the hypothalamic-pituitary-adrenal (HPA) axis to neonatal programming (Schapiro 1965, Levine & Mullins 1967, Sapolsky & Meaney 1986, Shanks et al 2000, we have recently shown that perinatal exposure to androgens can permanently affect the HPA axis phenotype in the adult female rat (Seale et al 2005). Another critical period during which gonadal steroids can activate numerous adult-specific physiological and neurobehavioural traits is puberty.…”
Section: Introductionmentioning
confidence: 99%